The Body Mass Index and the menstrual pattern of female adolescents in Gebangmalang Village, Mojoanyar District, Mojokerto Regency.: Array - Zulfa Rufaida; Sri Wardini Puji Lestari; Ika Yuni Susanti (LPPM STIKes Buleleng, 2020)
A woman's menstrual cycle is influenced by the Body Mass Index. This is caused by the presence of fat that accumulates in a woman's body which can affect the body temperature levels which will cause irregular menstruation. The research objective was to determine the relationship between the Body Mass Index and the menstrual pattern of female adolescents in Gebangmalang Village, Mojoanyar District, Mojokerto Regency. This type of research uses analytical research. The independent variable is the Body Mass Index, while the dependent variable is the menstrual pattern. The study population was all young women in Gebangmalang Village, Mojoanyar District, Mojokerto Regency as many as 430 people with a sample of 207 people who were taken using simple random sampling. The instrument for calculating BMI used microtoise and weight scales, while for menstrual patterns used an interview sheet. The results showed that of the 93 respondents who had normal BMI experienced normal menstrual patterns as many as 77 people (83%). The results of the Wilcoxon statistical test at the level of significance Î± = 0.05 indicated that Ï = 0.000, which means that there is a relationship between the Body Mass Index and the menstrual pattern of young women. Young women who have a high Body Mass Index tend to experience menstrual pattern disorders. For this reason, it is recommended that young women pay attention to body weight and BMI so that they do not experience interference with their menstrual patterns.